The body and the screen: theories of internet spectatorship - White, Michele (Massachusetts Institute of Techonology, 2006)
Internet and computer users are often represented onscreen as active and empowered―as in AOL's striding yellow figure and the interface hand that appears to manipulate software and hypertext links. In The Body and the Screen Michele White suggests that users can more properly be understood as spectators rendered and regulated by technologies and representations, for whom looking and the mediation of the screen are significant aspects of engagement. Drawing on apparatus and feminist psychoanalytic film theories, art history, gender studies, queer theory, critical race and postcolonial studies, and other theories of cultural production, White conceptualizes Internet and computer spectatorship and provides theoretical models that can be employed in other analyses. She offers case studies and close visual and textual analysis of the construction of spectatorship in different settings. White shows that despite the onscreen promise of empowerment and coherence (through depictions of materiality that structure the experience), fragmentation and confusion are constant aspects of Internet spectatorship. She analyzes spectatorship in multi-user object-oriented settings (MOOs) by examining the textual process of looking and gazing, contrasts the experiences of the women's webcam spectator and operator, describes intentional technological failures in net art, and considers ways in which traditional conceptions of artistry, authorship, and production techniques persist in Internet and computer settings (as seen in the creation of virtual environment avatars and in digital imaging art). Finally, she analyzes the physical and psychic pain described by male programmers in Internet forums as another counternarrative to the common tale of the empowered user. Spectatorship, White argues, not only affects the way specific interfaces are understood but also helps shape larger conceptions of self and society.